Adding "Student Voice" to the Mix: Perception Surveys and State Accountability Systems - Jack Schneider; James Noonan; Rachel S. White; Douglas Gagnon; Ashley Carey (SAGE Publishing, 2021)
For the past two decades, student perception surveys have become standard tools in data collection efforts. At the state level, however, "student voice" is still used sparingly. In this study, we examine the ways in which including student survey results might alter state accountability determinations. Reconstructing the accountability system in Massachusetts, we draw on a unique set of student survey data, which we add to the state's formula at a maximally feasible dosage in order to determine new school ratings. As we find, student survey data shift school accountability ratings in small but meaningful ways and appear to enhance functional validity. Student survey results introduce information about school quality that is not captured by typical accountability metrics, correlate moderately with test score growth, and are not predicted by student demographic variables.